Pentingnya Optimalisasi Strategi Marketing UMKM Dapoer Rendang Riery Melalui Platform Digital Di Kota Payakumbuh - Henny Wati; Patria Nagara; Agus Nurofik; Deby Handayani; Sudirman, Sudirman; Syukrial, Syukrial (CV. ITTC INDONESIA, 2025)
This community service activity, focusing on the importance of optimizing the marketing strategy of Dapoer Rendang Riery, an MSME, through digital platforms in Payakumbuh City, aims to foster participants' enthusiasm for using digital platforms to increase sales and ultimately generate greater profits. Currently, many MSMEs are unfamiliar with digital platforms. Therefore, this activity aims to improve their marketing system, enabling them to gain wider recognition and international reach.